A highly active molybdenum multisulfide electrocatalyst for the hydrogen evolution reaction. Issue 109 (9th November 2016) - Zhang, Li-Fang; Ou, Gang; Gu, Liu; Peng, Zhi-Jian; Wang, Lu-Ning; Wu, Hui
Abstract : We prepared a molybdenum multisulfide electrocatalyst, which exhibits superior activity in acid media, surpassing most existing molybdenum-sulfide-based catalysts. Abstract : We prepared a highly active molybdenum multisulfide (MoS x ) hybrid material by an arc-melting method, which exhibits superior activity in acid media with a low overpotential of 156 mV at j = 10 mA cm −2, and a Tafel slope of 58 mV dec −1, surpassing most existing molybdenum-sulfide-based catalysts.